A Proposed Model of Household Waste Separation Behavior: Pilot Test and Instrument Validation - Mohd Nasir, Syukrie; Shafii, Haryati; Md Yassin, Azlina (Journal of Social Transformation and Regional Development, 2021)
Due to the increasing waste generation over the years in Malaysia, there is an urgent need to address this problem by implementing effective household waste separation initiatives. Although past studies have tried to explain the waste behavior from psychological perspective, there is little understanding as to the impact of environmental ethics and specific waste separation knowledge towards waste separation behavior. The aims of this article are to present questionnaire development based on waste separation behavior proposed model, pre-test, pilot test and findings. After obtaining 116 valid questionnaires from households in the district of Mersing, Johor, descriptive and factor analysis were conducted. The results from pilot test indicated that both specific waste separation knowledge and waste separation at source behavior were moderate. Early findings indicate that most of households reject the anthropocentric and technocentric ethics orientation. From the factor analysis, it can be concluded that the proposed model intended to predict SAS behavior warrant minor amendments which enable the model to be used in the future study. The valid and reliable instrument has a potential to better understand the underlying SAS behavior among households in Malaysia.